Exploring geo-tagged photos to assess spatial patterns of visitors in protected areas : the case of park of Etna (Italy) - Signorello, Giovanni; Farinella, Giovanni Maria; Di Silvestro, Lorenzo; Torrisi, Alessandro; Gallo, Giovanni (My University, 2018)
In this paper we use the georeferenced images publicly available on Flickr platform as a source of information to monitor visitors in nature areas. In particular, we propose and evaluate a method composed by three main steps to perform the analysis of social images related to natural park of Mount Etna. At first metadata of the georeferenced images are explored to identify trends, patterns and relationships among the information acquired. Then data mining techniques are used to generate a traveling model. Association rules that highlight locations visited jointly are identified using the Apriori data mining technique. Finally, we consider places that are likely to be jointly visited and analyze the tourist flow from one to another.
Keywords: Georeferenced Data, Digital Footprints, Flickr, Recreation, Protected Areas, Data Mining, Apriori Algorithm; 004